Body city : siting contemporary culture in India - Chandrasekhar, Indira; Seel, Peter C. (Berlin : Haus Der Kulturen Der Welt ; Delhi : Tulika Books, 2003)
Contributed articles on post 1947 Indian culture and traditions.
"In memory of Bhupen Khakhar 10 March 1934- 8 August 2003": T.p. verso.
Includes bibliographical references.
Keywords: India -- Civilization